Veganize it! : easy DIY recipes for a plant-based kitchen - Robertson, Robin (Robin G.) (Houghton Mifflin Harcourt, 2017)
Provides vegan staple recipes, including tempeh bacon, tofu feta, and vegan butter to make main dishes, sides, beverages, and desserts.